(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The postgenocidal diaspora is over 100 years old. For a century, all educational institutions of the diaspora, without exception, have tried to build their identity in new conditions. They built a church, a school, cultural and trade union institutions, organizations in their midst and became 239 Armenian communities, where a new life for the Armenian diaspora that survived the genocide was born. This article discusses the activities of the National Karen Yeppe Jemaran in Aleppo since 1947 to preserve the Armenian identity and national education of the community, noting that Jemaran is the only secondary school where 100% of the students are Armenian.